Dietary ginger (Zingiber officinale) enhances performance traits, biochemical and haematological indices of Turkey targeting mRNA gene expression - Eman A. Manaa; Mervat A. Abdel-Latif; Samya E. Ibraheim; Abdelaziz M. Sakr; Hanaa M. Ghanem; Rania M. Waheed; Ghadeer M. Albadrani; Mohamed M. Abdel-Daim; Amr El Zawily; Basant M. Shafik (Animal Biotechnology)
Ginger rich in polyphenols, possesses various biomedical properties. Researchers investigated the effects of dietary ginger supplementation on turkey performance traits, biochemical parameters, haematological parameters and mRNA gene expression. Ginger root powder was administered at different doses (0, 10, 20 and 40 g/kg) to the turkeys. Notably, the 20 g/kg group exhibited improved performance traits and a higher broiler production efficiency factor (BPEF). Importantly, ginger was found to be safe for turkeys based on serum indices. Furthermore, the expression of several growth-related genes, including growth hormone receptor (GHR), insulin-like growth factor 1 (IGF-1), adenine nucleotide translocase (ANT), cyclooxygenase 3 (COX-3) and uncoupling protein 3 (UCP-3), was upregulated in the 20 g/kg enhancing their growth performance and economic efficiency in addition to keeping their health status safe. Therefore, Ginger root powder can be supplemented for turkey at a concentration of 2% as the addition of ginger powder is a long-term process.